PENGARUH PRAKTIK JARIMATIKA TERHADAP KETERAMPILAN BERHITUNG PERKALIAN PADA SISWA KELAS II SD (Universitas Negeri Semarang, 2016)
This research was to determine the effect of the arithmetics Jarimatika practice towards multiplication skills in second grade Elementary School cluster of Jogonegoro Selomerto, Wonosobo District. The population in this study was second grade Elementary School cluster of Jogonegoro which is amounted 8 schools. The type of the research was quasy experiment by using the type of the randomized control gourp pretest-posttest design. The sampling system used in the reserarch was cluster random sampling method which takes in two steps randomly. The first step got 5 class samples and second step got 3 classes. Analysis of hypothesis testing is using SPSS version 20, that produced: (1) There was influence of Jarimatika aplication to the multiplication numeracy skills, value df = 40 obtained by the Sig. (2-tiled) 0024, then H0 was rejected. (2) Jarimatika practice increased the multiplication numeracy skills. The analysis of N-Gain know to increase numeracy skills in the experimental class at 0.411. While control class only 0.135.